2024
DOI: 10.3390/curroncol31010023
|View full text |Cite
|
Sign up to set email alerts
|

Counselling Framework for Germline BRCA1/2 and PALB2 Carriers Considering Risk-Reducing Mastectomy

Stephanie M. Wong,
Carla Apostolova,
Elisheva Eisenberg
et al.

Abstract: Female BRCA1/2 and PALB2 germline pathogenic variant carriers have an increased lifetime risk of breast cancer and may wish to consider risk-reducing mastectomy (RRM) for surgical prevention. Quantifying the residual lifetime risk and absolute benefit from RRM requires careful consideration of a patient’s age, pathogenic variant, and their personal history of breast or ovarian cancer. Historically, patients have been counselled that RRM does not necessarily prolong survival relative to high-risk surveillance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Bilateral RRM confers a substantial reduction in breast cancer risk for unaffected individuals with PVs in BRCA1–2 genes, estimated at 90% and up to 95% when combined with RRSO [ 45 , 46 , 47 , 48 ]. Regarding mortality risk, a recent population-based cohort study reported that it was lower among unaffected individuals with PVs in the BRCA1 gene who underwent bilateral RRM compared to those under surveillance, though this effect was not observed in unaffected individuals with PVs in the BRCA2 gene [ 47 , 48 ]. The annualized cumulative incidence rate of contralateral breast cancer among unilateral breast cancer cases with germline PVs in BRCA1 and BRCA2 genes is 2.3% and 1.7% per year, respectively [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral RRM confers a substantial reduction in breast cancer risk for unaffected individuals with PVs in BRCA1–2 genes, estimated at 90% and up to 95% when combined with RRSO [ 45 , 46 , 47 , 48 ]. Regarding mortality risk, a recent population-based cohort study reported that it was lower among unaffected individuals with PVs in the BRCA1 gene who underwent bilateral RRM compared to those under surveillance, though this effect was not observed in unaffected individuals with PVs in the BRCA2 gene [ 47 , 48 ]. The annualized cumulative incidence rate of contralateral breast cancer among unilateral breast cancer cases with germline PVs in BRCA1 and BRCA2 genes is 2.3% and 1.7% per year, respectively [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The annualized cumulative incidence rate of contralateral breast cancer among unilateral breast cancer cases with germline PVs in BRCA1 and BRCA2 genes is 2.3% and 1.7% per year, respectively [ 49 , 50 ]. Due to this increased risk, some may be considered for contralateral RRM, although the oncological benefits are not clear given that their prognosis is primarily dictated by their primary breast cancer [ 48 , 51 , 52 ]. This evidence underscores the need for more individualized counseling based on the BRCA variant type and the difficulties inherent in choosing between bilateral RRM and breast cancer surveillance among unaffected and affected carriers [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%